Development of hybrid small molecules that induce degradation of estrogen receptor‐alpha and necrotic cell death in breast cancer cells. Issue 11 (11th October 2013) - Okuhira, Keiichiro; Demizu, Yosuke; Hattori, Takayuki; Ohoka, Nobumichi; Shibata, Norihito; Nishimaki‐Mogami, Tomoko; Okuda, Haruhiro; Kurihara, Masaaki; Naito, Mikihiko
Abstract : Manipulation of protein stability with small molecules has a great potential for both basic research and clinical therapy. Recently, we have developed a series of hybrid small molecules named SNIPER (S pecific andN on‐geneticI AP‐dependentP roteinER aser) that induces degradation of target proteins via ubiquitin‐proteasome system. Here we report the activities of SNIPER(ER) that targets estrogen receptor alpha (ERα) for degradation. SNIPER(ER) induced degradation of ERα and inhibited estrogen‐dependent expression of pS2 gene in an estrogen‐dependent breast cancer cell line MCF‐7. A proteasome inhibitor MG132 and siRNA‐mediated downregulation of cIAP1 abrogated the SNIPER(ER)‐induced ERα degradation, suggesting that the ERα is degraded by proteasome subsequent to cIAP1‐mediated ubiquitylation. Intriguingly, after the ERα degradation, the SNIPER(ER)‐treated MCF‐7 cells undergo rapid cell death. Detailed analysis indicated that SNIPER(ER) caused necrotic cell death accompanied by a release of HMGB1, a marker of necrosis, from the cells. Following the ERα degradation, reactive oxygen species (ROS) was produced in the SNIPER(ER)‐treated MCF‐7 cells, and an anti‐oxidant N‐acetylcysteine inhibited the necrotic cell death. These results indicate that SNIPER(ER) induces ERα degradation, ROS production and necrotic cell death, implying a therapeutic potential of SNIPER(ER) as a lead for the treatment of ERα‐positive breast cancers.